The Modality of the Future: A Default-Semantics Account - Jaszczolt, K.M. (Proceedings of the Amsterdam Colloquium, 2003)
I discuss three types of use of English will: regular future, dispositional necessity, and epistemic, and demonstrate that they can be accounted for by one semantic representation which I call compositionality-intentionality merger. For this purpose, I propose to introduce into DRT an acceptability operator ACCp ('it is acceptable to a degree n of the mode of presentation delta. that p') where the scalar value n determines the type of use of will. I demonstrate that an analogous scalar analysis applies to various ways of expressing futurity such as regular future, futurative progressive and tenseless future. The principles of Default Semantics correctly predict the existence of a default interpretation among the possible uses of will on the one hand, and possible expressions of futurity on the other.